Simultaneous Determination and Method Validation of Methamphetamine and Its Metabolite Amphetamine in Rat Liver Using GC-FID - Wijittra Kaewnam (Prince of Songkla University, 2016)
Thesis (M.Sc., Forensic Science)--Prince of Songkla University, 2011